Study Of Ecological, Social, Spiritual Aspects Towards Sustainable Environmental Management in Wiyantri Village, Skanto Sub District, Keerom Regency, Papua Province, Indonesia - Antoh, Alfred Alfonso; Akobiarek, Maik Nataniel Ruben; Mawarni, Dita (Journal of Ecohumanism, 2024)
Sustainability research is a type of research that examines the sustainable management of natural resources and is an important part of maintaining natural resources in a sustainable manner. The increase in world population is currently high enough that it is necessary to maintain traditional values in society in protecting our environment so that it can be enjoyed by generations. For this reason, sustainability research or studies are very important to continue to develop. This study aims to determine how to assess sustainability through ecological, socio-cultural and spiritual aspects in the community in Wiyantri Village, Skanto District, Keerom Regency. To assess whether an environment is deteriorating or not in terms of ecological, socio-cultural, and spiritual aspects. The method used in this research is the Community Sustainability Assessment (CSA) and the sample is selected intentionally (purposive sampling). The results of the study in assessing community sustainability in Wiyantri Village, Skanto District, Keerom Regency. From the data that has been obtained from the ecological aspect, socio-cultural aspect and spiritual aspect, it is known that the total of each aspect shows very good progress showing sustainability with a score of 999+ on Jalan Lotus with score 1070. Then the location that shows a good start towards sustainability with a score of 500-998 is Jalan Mawar with a total score of 575.